Estudo de associações entre o exame clínico ultrassonográfico com a bioimpedância elétrica na avaliação hemodinâmica de pacientes adultos sépticos. - Antonio Tolentino Nogueira de Sá (2021)
Introduction: Sepsis is an important cause of morbidity and mortality in Intensive Care Units (ICU) around the world. Treatment should be planned with the aim of optimizing oxygen supply to adequate tissue perfusion. Planned fluid infusion should be guided by monitoring of fluid status and cardiac performance. In the non-invasive form, ultrasonography (US) has been gaining access to the hemodynamic and blood volume assessment, but subject to observerdependent variations. Alternatively, there are measurements of cardiac output, blood volume and pulmonary water by bioelectrical impedance. This study aimed to analyze associations between non-invasive ultrasound and bioelectrical impedance measurements for the assessment of cardiac performance, pulmonary edema and blood volume in adult, septic patients admitted to an intensive care unit. Methods: Cross-sectional study with a sample of 33 patients, carried out from August 2018 to October 2019 in the ICU of a private hospital in Belo Horizonte/Minas Gerais. Pulmonary assessment by US determined the presence or absence of edema (pattern B or A). In the qualitative cardiac assessment (4 windows), it was classified as normal or depressed. In the assessment of volemia by US vena cava, patients were classified as normovolemic or hypervolemic (variation below 50%) and hypovolemic (variation greater than 50%). In the evaluation by bioelectrical impedance, the following measures were used: Cardiac Index (CI): depressed (less than 2.5 L/min/m2) or normal (greater than 2.5 L/min/m2). GoorGravone Index (GGI): depressed (below 10 - Ejection Fraction less than 55%) or normal (> 10). Cardiac Power Index (CPI): depressed (<0.45 w/m2) or normal (>0.45 w/m2). Total body water (TBW): below 40%, hypovolemia, above 63%, hypervolemia. To verify the association between bioimpedance characteristics and ultrasound variables, the chi-square or Fischer's exact test was used, and to control for other factors, the Mantel-Haenszel test was used. A significance level of 5% (p value ≤ 0.05) was adopted. Sensitivity and specificity analyzes were performed using Receiver Operator Characteristic Curves. Agreement was analyzed using the Kappa test. Results: Of the 33 patients with sepsis, 60.6% were male, 36.4% with a pulmonary focus of infection, with a SAPS 3 measurement of 62.4 points. When the associations of ultrasound variables (pulmonary edema and cardiac performance, cava variation) with bioimpedance variables (TBW, CPI, GGI, IC) were evaluated, the absence of a statistically significant association was observed (p> 0.05). There was no statistical significance in the evaluation for sensitivity, specificity and agreement (p> 0.05). Conclusion: In the assessment of cardiac performance, blood volume and pulmonary edema in septic patients in ICUs, data obtained by electrical bioimpedance are not associated with data obtained by clinical evaluation and ultrasonography.